Biodegradation of a medium-chain-length polyhydroxyalkanoate in tropical river water - Ho, Y.H.; Gan, S.N.; Tan, I.K.P. (2002)
The medium-chain-length polyhydroxyalkanoate (PHA(MCL)) produced by Pseudomonas putida PGA1 using saponified palm kernel oil as the carbon source could degrade readily in water taken from Kayu Ara River in Selangor, Malaysia. A weight loss of 71.3 of the PHA film occurred in 86 d. The pH of the river water medium fell from 7.5 (at d 0) to 4.7 (at d 86), and there was a net release of CO(2). In sterilized river water, the PHA film also lost weight and the pH of the water fell, but to lesser extents. The C8 monomer of the PHA was completely removed after 6 d of immersion in the river water, while the proportions of the other monomers (C10, C12, and C14) were reversed from that of the undegraded PHA. By contrast, the monomer composition of the PHA immersed in sterilized river water did not change significantly from that of the undegraded PHA. Scanning electron microscopy showed physical signs of degradation on the PHA film immersed in the river water, but the film immersed in sterilized river water was relatively unblemished. The results thus indicate that the PHAMCL was degraded in tropical river water by biologic as well as nonbiologic means. A significant finding is that shorter-chain monomers were selectively removed throughout the entire PHA molecule, and this suggests enzymatic action.